2001
DOI: 10.1037/0893-164x.15.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of depression and survival experience among three samples of smokers trying to quit.

Abstract: Symptoms of depression have been associated with increased smoking prevalence and failure to quit smoking in several cross-sectional and population-based studies. Few studies, however, have prospectively examined the ability of current symptoms of depression to predict failure to quit smoking in treatment-motivated smokers. Pretreatment depressed mood was assessed by 3 different methods in 3 separate samples, 2 of which comprised smokers receiving combined pharmacological and behavioral treatments and a 3rd in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
137
2
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(158 citation statements)
references
References 25 publications
17
137
2
2
Order By: Relevance
“…Thus, it may be tempting to ascribe most of the differences noted above to depression, because it is well documented that both those with diabetes and smokers in general are more likely to report depression, and that smokers who are depressed have more diffi culty quitting. [28][29][30][31][32] Our question, however, is not a validated way to identify clinical depression. Unlike Ciechanowski et al, 33 who found depression severity was associated with poorer adherence to diabetic regimens, we could fi nd no clear relationship between these reports of often feeling depressed and either diabetes self-care practices or physical activity levels.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it may be tempting to ascribe most of the differences noted above to depression, because it is well documented that both those with diabetes and smokers in general are more likely to report depression, and that smokers who are depressed have more diffi culty quitting. [28][29][30][31][32] Our question, however, is not a validated way to identify clinical depression. Unlike Ciechanowski et al, 33 who found depression severity was associated with poorer adherence to diabetic regimens, we could fi nd no clear relationship between these reports of often feeling depressed and either diabetes self-care practices or physical activity levels.…”
Section: Discussionmentioning
confidence: 99%
“…Because mild levels of depressive symptomatology have been associated with a resumption of smoking, independent of nicotine dependence (33), depressive symptoms also may decrease a woman's motivation to remain abstinent postpartum. Thus, both changes in mood and concerns about body shape and weight may play a role in women's attitudes toward smoking during the postpartum period (34).…”
Section: Introductionmentioning
confidence: 99%
“…19 Depression status may influence patients' ability to engage in smoking cessation. 6,7,9 Some evidence supports that smokers with current depression are less likely to succeed with smoking cessation compared to history positive patients.…”
mentioning
confidence: 99%
“…[3][4][5] Smokers with depression are more likely to relapse from a quit attempt, have higher nicotine dependence, suffer negative mood symptoms from withdrawal, and suffer greater smoking-related morbidity and mortality than the general population of smokers. [6][7][8][9][10][11][12] For the general population, effective smoking cessation interventions include nicotine replacement therapy (NRT), 13 antidepressants bupropion and nortriptyline, 14 nicotine receptor partial agonists varenicline, 15 and smoking cessation counseling. [16][17][18] Pharmacological and behavioral strategies increase the likelihood of successful quits attempt by 1.5 to 2 times compared to placebo or usual care.…”
mentioning
confidence: 99%